Peningkatan Aktivitas dan Hasil Belajar Siswa dengan Metode Kooperatif Tipe STAD (Student Teams Achievement Division) Kelas V SD Negeri 08 Talao - Nur Asni; Joni Iskandar (Kampus Akademik Publiser, 2024)
This research is motivated by several problems that occur in the learning activities of SD Negeri 08 Talao, so that the activities and learning outcomes obtained by students have not reached the established KKM. Based on observations, it is known that passive student activities in following the learning process and the lack of teacher variation in using methods affect the low learning outcomes and learning activities of students. The purpose of this study is to determine the increase in student activity and learning outcomes of grade V students of SD N 08 Talao in learning using the STAD (Student Teams Achievement Division) type cooperative method. This research is included in Classroom Action Research (CAR) which is carried out in two cycles. One cycle consists of 4 stages of activity, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The subjects of this study were grade V students of SD Negeri 08 Talao with a total of 18 students consisting of 10 male students and 8 female students. Data collection techniques used in this study were qualitative and quantitative data analysis. The results of this study indicate that student learning activity in cycle I was 58%, and in cycle II it increased by 20% to 79%. For student learning outcomes that achieved the Minimum Completion Criteria (KKM), the average completion rate in cycle I was 56%, and in cycle II it increased by 22% to 78%. The indicator of success in this study is an increase in student activity and learning outcomes, indicated by the achievement of the minimum completion criteria (KKM), with an average completion rate of 75% in subtheme 1.